Why do individuals choose a career in music? A Systematic review of socialization-, motivation-, and identity-based factors - Váradi, Judit; Szűcs, Tímea (Central European Journal of Educational Research, 2026)
The process of choosing a career in music is a complex and multifaceted phenomenon that requires the integration of motivational, socialization-based, and identity-oriented perspectives for its comprehensive understanding. The aim of the present systematic literature review is to identify and synthesize empirical studies examining music career choice, particularly within the context of professional higher music education, in relation to identity formation, the quality of motivation, and career-orientation decisions. The review includes 20 studies published between 2003 and 2025, representing considerable methodological heterogeneity as well as broad geographical and cultural diversity. Based on the thematic analysis, four overarching thematic domains were identified: (1) socialization and environmental factors, (2) motivational structures and career intentions, (3) identity development and identity conflicts, and (4) the influence of institutional and educational contexts. The findings indicate that, in music career choice, musician identity generally takes precedence over teacher identity, while extrinsic motivational factors play a significant role in decisions to pursue music teaching careers. Furthermore, early socialization experiences—particularly the influence of parents and first instrumental teachers—have a long-term impact on career orientation. The review also highlights that higher education institutions do not always consciously exploit their potential role in shaping professional identity. Effective interventions therefore require multi-level, developmentally oriented approaches, including the provision of early teaching experiences, the strengthening of mentoring practices, and the introduction of portfolio-career perspectives.